Efektifitas Model Pembelajran Inqury Tipe Pictorial Riddle dalam Meningkatkan Kemampuan Berfikir Kritis Siswa pada Mata Pelajaran Fiqih pada Siswa XI Madrasah Aliyah Darul Qolam Kab. Bandung - Reni Mulyani; Aep Saepudin; Fitroh Hayati (UNISBA Press, 2022)
Abstract. One of the problems faced by the world of education is the weakness of the learning process. In the learning process, children are less encouraged to develop thinking skills. The learning process in the classroom is directed at the ability to memorize information, the child's brain is forced to remember and hoard various information it remembers to relate it to everyday life. As a result, when children graduate from school, they are theoretically smart, but they are poor in application. This thesis discusses the effectiveness of the pictorial riddle type inquiry learning model in improving students' critical thinking skills in fiqh subjects, with the aim of (1) knowing the students' abilities before implementing the pictorial riddle type inquiry learning model in improving students' critical thinking skills in fiqh subjects. at MA Darul Qolam Bandung?(2)To determine students' critical thinking skills after using the Pictorial Riddle-type inquiry learning model in Fiqh subjects at MA Darul Qolam Bandung?(3) To determine the effect of the Pictorial Riddle-type inquiry learning model on students' critical thinking skills in Fiqh subjects at MA Darul Qolam Bandung. The type of this research is experimental quantitative research with Control Group Design research design. The population in this study were all students of class XI MA Darul Qolam Kab. Bandung as many as 40 students. The sampling technique in this research is purposive sampling. The number of samples used was 19 students where in class XI MAB with 19 students selected as the experimental class taught by the pictorial riddle-type inquiry learning model and class XI MAA with 21 students selected as the control class taught by direct learning. The data collection technique was carried out using a test instrument in the form of multiple choice as many as 20. The data analysis technique was carried out using descriptive analysis techniques and inferential analysis techniques. The results obtained in the class using the pictorial riddle-type inqury learning model with an average value of 77. Student learning outcomes without using the pictorial riddle-type inqury learning model obtained an average value of 57. This indicates that there is a significant effect between the models. pictorial riddle-type inqury learning on critical thinking skills of class XI MA Darul Qolam students, Bandung Regency. This is supported by the results of the regression analysis obtained by the value of tcount17 > ttable 0.02. Abstrak. Salah satu masalah yang dihadapi dunia pendidikan adalah lemahnya proses pembelajaran. Dalam proses pembelajaran, anak kurang didorong untuk mengembangkan kemampuan berfikir. Proses pembelajaran di dalam kelas diarahkan kemampuan untuk menghafal informasi,otak anak dipaksa untuk mengingat dan menimbun berbagai informasi yang diingatnya untuk menghubungkannya dengan kehidupan sehari-hari. Akibatnya, ketika anak lulus dari sekolah, mereka pintar secara teoritis, tetapi mereka miskin aplikasi. Skripsi ini membahas tentang efektifitas model pembelajaran inqury tipe pictorial riddle dalam meningkatkan kemapuan berfikir kritis siswa pada mata pelajaran fiqih, dengan tujuan(1)Untuk mengetahui kemampuan peserta didik sebelum dilaksakanannya model pembelajaran inquiry tipe pictorial riddle dalam meningkatkan kemampuan berpikir keritis siswa pada mata pelajaran fiqih di MA Darul Qolam Bandung ?(2)Untuk mengetahui kemampuan berpikir kritis siswa setelah menggunakan model pembelajaran inquiry tipe Pictorial Riddle pada mata pelajaran Fiqih di MA Darul Qolam Bandung?(3) Untuk mengetahui pengaruh model pembelajaran inquiry tipe Pictorial Riddle terhadap kemampuan berpikir keritis siswa pada mata pelajaran Fiqih di MA Darul Qolam Bandung. Jenis penelitian ini adalah penelitian kuantitatif eksperimen dengan desain penelitian Control Group Design. Populasi pada penelitian ini adalah seluruh siswa kelas XI MA Darul Qolam Kab.Bandung sebanyak 40 siswa. Teknik pengambilan sampel pada penelitian ini adalah purposive sampling. Jumlah sampel yang digunakan sebesar 19 siswa dimana pada kelas XI MAB dengan jumlah siswa 19 terpilih sebagai kelas eksperimen yang diajar dengan model pembelajaran inqury tipe pictorial riddle dan kelas XI MAA dengan jumlah siswa 21 terpilih sebagai kelas kontrol diajar dengan pembelajaran langsung. Teknik pengumpulan data dilakukan dengan menggunakan instrumen tes berbentuk pilhan ganda sebanyak 20. Teknik analisis data dilakukan dengan menggunakan teknik analisis deskriptif dan teknik analisis inferensial. Hasil penelitian yang diperoleh pada kelas yang menggunakan model pembelajaran inqury tipe pictorial riddle dengan nilai rata-rata 77. Hasil belajar siswa tanpa menggunakan model pembelajaran inqury tipe pictorial riddle diperoleh nilai rata-rata sebesar 57. Hal ini menunjukkan bahwa terdapat pengaruh yang signifikan antara model pembelajaran inqury tipe pictorial riddle terhadap kemapuan berpikir kritis siswa kelas XI MA Darul Qolam Kab.Bandung. Hal ini didukung oleh hasil analisis regresi diperoleh nilai thitung17 >ttabel0,02.